Мирнодолинський скарб коваля-ювеліра з Харківщини - Колода, В.В.; Скиба, А.В. (Археологія і давня історія України, 2021)
У статті проаналізовано речовий комплекс виявлений в Харківської обл. поблизу раніше не відомого селища з матеріалами пеньківської та салтівської археологічних культур раннього середньовіччя. За речовим складом комплекс являє собою скарб коваля-ювеліра і датується серединою — другою половиною VII ст. Артефакти чорної металургії представлені ковальськими інструментами (ковадлом і парою молотків) та сировиною (ковальські криці, заготовки для виробів). Артефакти ювелірного виробництва представлені унікальною серією матриць для виготовлення прикрас поясного набору та бронзовою сировиною, серед якої особливу увагу привертають сильно зношені монети пізньоримського часу. Цей комплекс є не тільки черговим підтвердженням високої майстерності ранньосередньовічних ремісників Східної Європи, а й свідченням того, що в означений час коваль поєднував якісну роботу по створенню виробів з чорного металу, бронзоливарництво та ювелірну справу. The stash of a smith jeweller, who worked with both black and colored metals, are analyzed in the article; they were found near Myrna Dolyna village on Kharkivschina. The following features allow to refer this complex to the southeastern part of the Penkov culture area: a discovery site, detected belt details of a heraldic style, as well as the matrices for their craft, and also parallels of the belt garniture with Dnipro treasures and complexes from other regions. The most reliable dating of the stash is middle-second half of the 7th century. Presence of the smith’s tools (anvil and two hammers; fig. 2: 1—3), and also a considerable amount of raw materials, semi-products, pieces and black metal subproducts (fig. 2: 4—11; 3) point to the fact, that a craftsman professionaly made blacksmithґs work orders. A wider range of analogies of metal working tools can be observed rather in the Saltov culture than on the synchronous sites of the East slavs. It shows the influence of the Khazarian populationґs smithcraft on neighbouring Slavic tribes. Beside smithcraft, a creftsman professionally worked with colored metal; colored raw material (bronze) supply for casting and jewellery (fig. 4), and also matrices for belt details production point to this fact. Apart from products made of colored metal junk, he also used Late Roman coins (fig. 7) as raw materials, which was detected for the first time in the context of Early Medieval treasures. Complex of colored repoussage artefacts represents a range of jewellery technologic stages: matrices for belt details manufacture and raw cast subproducts for matrices production (one of morphological types presented by both a finished plate and anologic matrix for their crafting; fig. 5: 4, 5), which was detected for the first time in Ukraine. A part of finished products (fig. 5: 1—3; 6: 4) could serve as patterns for analogic products, be under repair or intended to be melted as metal junk. The artefacts of this stash have a wide and interesting range of typological and stylistic analogies. A part of them refers to the Azov and Black Sea steppes, Crimean Mountains and Northern Caucasus (fig. 5: 1-2). Another part has wider parallels including particularly «the Antes’ antiquities» of the Dnipro region (fig. 6: 1—5). Some artefacts do not have any direct analogies (fig. 5: 3, 6, 7). Separate products (fig. 5: 4, 5) have parallels on the Slavic sites of the Eastern European forest steppe, in the Avar antiquities of the Pannonian Plane and Lombardic burial sites in Italy, but they are not common to the nomadic complexes of the Syvash type, Crimea or the Caucasus. Horizontal and symmetric plates with etched drawings in the form of dots and braces (fig. 5: 8, 9) tend to the Danube region, Italy, and also South Western Crimea. On the whole, among the range of analogies to the bronze products of the stash from Myrna Dolyna, we can distinguish these main directions: above the Black Sea region — Crimea — the Northern Caucasus and the Eastern European forest steppe — the Pannonian Plane — Italy. Taking into account a cultural-chronological definition, a craftsmanґs professional diversity seems unique, since apart from jewellery, he practiced smithcraft as well. The defined range of parallels allows to admit that the stash’s owner, a craftsman — smith jeweller, could make work orders from both representatives of Slavic military aristocracy and nomads of the Northern Pryazovia and Prysyvash region.